Monomers for adhesive polymers: 11. Structure–adhesive properties relationships of new hydrolytically stable acidic monomers. Issue 12 (18th March 2013) - Catel, Yohann; Fischer, Urs Karl; Moszner, Norbert
Abstract: The synthesis of six new hydrolytically stable acidic monomers is described. Those monomers are N, N ‐disubstituted acrylamides bearing either a phosphonic acid group or a diphosphonic acid group. They were fully characterized using 1 H NMR, 13 C NMR and 31 P NMR spectroscopy and high‐resolution mass spectrometry. The copolymerization of each acidic monomer with N, N ′‐diethyl‐1, 3‐bis(acrylamido)propane was investigated using photo‐differential scanning calorimetry. Self‐etching enamel–dentin adhesives were formulated and evaluated in terms of both dentin and enamel adhesion. The influence of the monomer structure (nature of either the spacer or the acidic group, nature of the acrylamide substitution) on the adhesive properties is discussed. The adhesives based on 10‐( N ‐ethylacrylamido)decylphosphonic acid and 10‐( N ‐methylacrylamido)decylbisphosphonic acid are able to achieve a strong bond between a dental composite and both dentin and enamel. © 2013 Society of Chemical Industry Abstract : The acidic monomers1a, 1b, 2–5 were synthesized. Their photopolymerization behaviours and their adhesive properties were investigated. The key effect of acidic monomer structure on adhesion was evident.